PERHITUNGAN BREAK EVEN POINT MENGGUNAKAN METODE PERSAMAAN DAN METODE GRAFIK PADA PENAMBANGAN PASIR DI CV. PUTRA MANDIRI - Diana Purwandari; Agil Adrian (LPPM Universitas Bina Bangsa, 2024)
This research was carried out at CV. Putra Mandiri is a sand producing company with the best quality in East Priangan. The aim of this research is to find out the Break Even Point (BEP) at CV. Putra Mandiri in optimizing Profitability in 2022. The method used to calculate the Break Even Point is using the Equation Method and Graphic Method. Meanwhile, the analysis technique used in Break Even Point is a cost-volume-profit analysis technique, then the cost-volume-profit data obtained in the field is processed using calculations and presented in graphical form. After carrying out analysis in calculating the Break Even Point, it can be seen that CV. Putra Mandiri experienced a Break Even Point when sales reached IDR 19,141,033,708 or 35,391 truck units, so the mathematical equation is Revenue Cost (RC) = 2,105,513,708 Q – 53,193,506,922,400, where Q is the quantity or amount of production